High-pressure phases of CaCO3: Crystal structure prediction and experiment - Oganov, Artem R.; Glass, Colin W.; Ono, Shigeaki (Earth and planetary science letters, 2006)
Post-aragonite phase of CaCO3, experimentally known to be stable above 40 GPa [S. Ono, T. Kikegawa, Y. Ohishi, J. Tsuchiya, Post-aragonite phase transformation in CaCO3 at 40 GPa, Am. Mineral. 90 (2005) 667–671], is believed to be a major carbon-containing mineral in the Earth's mantle. Crystal structure of this mineral phase could not be solved using experimental data or traditional theoretical simulation methods and remained a controversial issue. Using a combination of advanced ab initio simulation techniques and high-pressure experiment, we have been able to determine the crystal structure of CaCO3 post-aragonite. Here, we performed simulations with the USPEX code [C.W. Glass, A.R. Oganov, and N. Hansen, (in preparation). USPEX: a universal structure prediction program], which is based on an evolutionary algorithm using ab initio free energy as the fitness function. This novel methodology for crystal structure prediction, which uses only the chemical composition as input, is described in detail. For CaCO3, we identify a number of energetically competitive structures, the most stable of which closely matches the experimental powder diffraction pattern and, in agreement with experiment, becomes more stable than aragonite above 42 GPa. This structure belongs to a new structure type, which is also adopted by the high-pressure post-aragonite phases of SrCO3 and BaCO3. It has 2 formula units in the orthorhombic unit cell (space group Pmmn) and contains triangular CO32− ions and Ca2+ ions in the 12-fold coordination. Above 137 GPa, a pyroxene-type structure (space group C2221) with chains of CO44− tetrahedra becomes more stable than post-aragonite. For MgCO3, this structure becomes more stable than magnesite above 106 GPa and is a good candidate structure for MgCO3 post-magnesite.